Menjaga Kesucian Perjalanan Akhir: Pelatihan Penyelenggaraan Jenazah Berlandaskan Syariat - Saadal Jannah; Rodiah, Rodiah (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (KKN) Batch VII of STIBA Makassar in Kurusumange Village, Maros Regency, is a form of field-based academic activity aimed at implementing the Tri Dharma of Higher Education. Observing the reality of the community with minimal religious guidance, this study aims to examine how students contribute to society through religious programs carried out during the KKN period. The method for implementing the service program began with mapping community problems and needs using SOAR Analysis. Subsequently, work programs were designed based on the community's needs. From the analysis conducted, several religious activities were formulated, including Social Services (BAKSOS), the Pious Children Festival, Short-Term Islamic Boarding School Programs, Muslimah Study Circles, Teaching Quranic Education Centers (TPA/TPQ), Funeral Management Training, Weekend Tahfiz, DIROSA (Adult Quranic Education) Teaching, and other activities. It can be concluded that these activities positively impacted the Kurusumange Village community, particularly in religious aspects, aligning with the objectives set for the KKN program.